2007
DOI: 10.1144/sp285.13
|View full text |Cite
|
Sign up to set email alerts
|

The Badenian evaporite basin of the northern Carpathian Foredeep as a model of a meromictic selenite basin

Abstract: The hydrography and brine flow patterns in the Middle Miocene (Badenian) evaporite basin of the northern Carpathian Foredeep (in Ukraine, Poland and the Czech Republic) are reconstructed based on studies of the peculiar, conformably oriented, bottom-grown gypsum crystals present in the selenite deposits along the basin margin. The crystal apices are turned in a similar horizontal direction that is interpreted as the product of consistent flow of the bottom brines during crystal formation. Similarly the regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 87 publications
0
35
0
1
Order By: Relevance
“…This idea was also accepted by Połtowicz (1993), Bukowski (2011), and Głuszyński and Aleksandrowski (2016). Similarly Bąbel and Bogucki (2007), who applied limnological terminology to the evaporite basin, suggested a meromictic lake model for the basin, in which halite deposition was restricted to the deepest monimolimnion zone. It was assumed that the selenite deposits were formed only in the well oxygenated and Ca-sulphate saturated mixolimnion zone, on the marginal platform or shelf only.…”
Section: Models Of the Evaporitic Basinmentioning
confidence: 93%
See 4 more Smart Citations
“…This idea was also accepted by Połtowicz (1993), Bukowski (2011), and Głuszyński and Aleksandrowski (2016). Similarly Bąbel and Bogucki (2007), who applied limnological terminology to the evaporite basin, suggested a meromictic lake model for the basin, in which halite deposition was restricted to the deepest monimolimnion zone. It was assumed that the selenite deposits were formed only in the well oxygenated and Ca-sulphate saturated mixolimnion zone, on the marginal platform or shelf only.…”
Section: Models Of the Evaporitic Basinmentioning
confidence: 93%
“…5E). These studies revealed the counter clockwise pattern of brine flow in the basin, interpreted as cyclonic circulation typical of the closed and semiclosed basins of the northern hemisphere (Bąbel 1996(Bąbel , 2002bBąbel et al 1999Bąbel et al , 2011Bąbel et al , 2015Bąbel and Becker 2006;Bąbel and Bogucki 2007). The Badenian basin is possibly the only ancient example where the cyclonic basinal water flow pattern has been detected.…”
Section: Palaeocurrent Analysismentioning
confidence: 96%
See 3 more Smart Citations